(untitled) (Communications in Computational Physics, 2023)
This paper studies the geometric boundary representations for Inverse Lax-Wendroff (ILW) method, aiming to develop a practical computer-aided engineering method without body-fitted meshes. We propose the signed distance function (SDF) representation of the geometric boundary and design an extremely efficient algorithm for foot point calculation, which is particularly in line with the needs of ILW. Theoretical and numerical analyses demonstrate that the SDF representation of geometric boundary can satisfy ILW’s needs better than others. The effectiveness and robustness of our proposed method are verified by simulating initial boundary value computational physical problems of Euler equation for compressible fluids.